Tantangan Mewujudkan Kurikulum Pendidikan Islami di Provinsi Aceh yang Menerapkan Syari’at Islam - Moharriadi Syafari; Teuku Zulkhairi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
This article discusses the actual challenges in realizing an Islamic education curriculum in Aceh. As a province that was given permission to enforce the application of Islamic Sharia, including in the field of education, in fact, Aceh has not succeeded in realizing the implementation of an Islamic education curriculum. In fact, Aceh Qanun Number 9 of 2015 concerning the Implementation of Education mandates that the education curriculum in Aceh can be taught Islamically. However, until now the guidelines for implementing the Islamic education curriculum have not been successful. So, what is the reason and what are the challenges faced? This is what is answered in this study. This research method is qualitative where the interviewees are in-depth education stakeholders, both executive and legislative. The results show that there are a number of challenges in realizing Islamic education in Aceh such as Islamic curriculum guidelines that are not yet concrete, budget restrictions by the Aceh Government, problems in a top leader, the absence of a writing team, and clashes with the central government to the weakness of the executive branch. The results of this study are expected to be used as evaluation material for the success of the agenda for realizing Islamic education in Aceh.